A Need for a Consensus on an Interpretation of a Reformed Confession? Karl Barth’s Interpretation of a Confession as a Basis for Further Discussion - Tshaka, RS (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The concept ‘confession’ continues to be viewed with suspicion especially in some South African theological circles. One of the reasons that it has acquired such a view is because it is interpreted by some as a condemnation on those who are not associated with it. The Reformed church in South Africa is locked up in squabbles with regard to the ‘obligatory powers’ that such a statement presupposes. This paper argues that the squabbles apparent in the reformed church today are not alien from the reformed church of yesterday. To display the similarities, the history of the Lutheran interpretation as well as the reformed interpretation of a confession is investigated. This paper then argues that the problem lies with the lack of consensus on what the essence of a confession is and therefore how it ought to be interpreted in the reformed church. In contrast to the Lutheran interpretation which seems to dissuade the authorship of other confessions, a reformed confession is treated as a temporal statement of faith.